Galangin promotes cell apoptosis through suppression of H19 expression in hepatocellular carcinoma cells. (2nd June 2020) - Zhong, Xiaowei; Huang, Siyi; Liu, Dianfeng; Jiang, Ziping; Jin, Qinglong; Li, Chengshun; Da, Liu; Yao, Qunyan; Wang, Dongxu
Abstract: Background: Galangin has been extensively studied as the antitumor agent in various cancers. However, the effect of galangin in hepatocellular carcinoma (HCC) remains elusive. Methods: Using RNA sequencing, the differential expression of lncRNA in human HCC cell line with highly metastatic potential (MHCC97H) cells treated with galangin was investigated. Furthermore, H19 expression pattern was also determined in MHCC97H cells following treatment with galangin. In addition, knockdown and overexpression of H19 was performed to analyze the effect of the expression pattern of H19 on cell apoptosis, cell cycle, migration, and invasion in HCC cells. Moreover, the in vivo effect of galangin on tumor development was also determined in nude mice. In order to analyze loss expression of H19 in vivo, clustered regularly interspaced short palindromic repeats/Cas9 (CRISPR/Cas9) was used. Results: Total of 50 lncRNAs were significantly differentially expressed in MHCC97H cells treated with galangin. Besides, the expression of H19 was markedly reduced following treatment with galangin in MHCC97H cells. Compared to the Control group, the galangin‐treated group inhibited cell migration and invasion. Knockdown of H19 expression showed increased cell apoptosis and decreased invasion. In addition, RNA‐seq data also identified 161 mRNA which was significantly differentially expressed following treatment with galangin. To further determine the underlying mechanism, p53 protein was analyzed. Notably, the results indicated that knockdown of H19 and miR675 induced the expression of p53, eventually promoting cell apoptosis in MHCC97H cells. These results indicated that galangin promoted cell apoptosis through reduced the expression of H19 and miR675 in MHCC97H cells. The in vivo result showed that compared to the Con, tumor growth was remarkably suppressed with loss expression of H19 . Conclusion: Our data suggested that galangin has a crucial role in hepatocarcinogenesis through regulating the expression pattern of H19 . Abstract : Amount 50 lncRNAs were differentially expressed in galangin‐treated by RNA‐Seq. H19 induced cell apoptosis through p53 protein after galangin treatment. Target knock out H19 expression using CRISPR/Cas9.